2013
DOI: 10.1371/journal.pone.0064799
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence, and a Sequence-Defined Genetic Linkage Map of the Legume Crop Species Lupinus angustifolius L

Abstract: Lupin (Lupinus angustifolius L.) is the most recently domesticated crop in major agricultural cultivation. Its seeds are high in protein and dietary fibre, but low in oil and starch. Medical and dietetic studies have shown that consuming lupin-enriched food has significant health benefits. We report the draft assembly from a whole genome shotgun sequencing dataset for this legume species with 26.9x coverage of the genome, which is predicted to contain 57,807 genes. Analysis of the annotated genes with metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 51 publications
(76 reference statements)
1
125
0
4
Order By: Relevance
“…Lupinus is the largest Genisteae genus, comprising 267 species, and appears to be monophyletic in origin (Ainouche and Bayer, 1999;Drummond et al, 2012). Chromosome numbers range between 2n = 24 to 2n = 52, and there are multiple lines of evidence showing that at least one polyploidy event has taken place since the divergence of Genisteae from other Papilionoid legumes (Wolko and Weeden, 1989;Gupta et al, 1996;Naganowska et al, 2003;Nelson et al, 2006;Parra-Gonzalez et al, 2012;Yang et al, 2013b;Kroc et al, 2014). The structural distinctiveness of Lupinus genomes from other Papilionoid genomes has been investigated by comparing genetic maps of L. angustifolius to the reference genome sequences of Medicago truncatula and Lotus japonicus Nelson et al, 2010) and by comparing the genetic map of L. albus to the genome of M. truncatula (Phan et al, 2007a).…”
Section: A Genus Lupinus Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Lupinus is the largest Genisteae genus, comprising 267 species, and appears to be monophyletic in origin (Ainouche and Bayer, 1999;Drummond et al, 2012). Chromosome numbers range between 2n = 24 to 2n = 52, and there are multiple lines of evidence showing that at least one polyploidy event has taken place since the divergence of Genisteae from other Papilionoid legumes (Wolko and Weeden, 1989;Gupta et al, 1996;Naganowska et al, 2003;Nelson et al, 2006;Parra-Gonzalez et al, 2012;Yang et al, 2013b;Kroc et al, 2014). The structural distinctiveness of Lupinus genomes from other Papilionoid genomes has been investigated by comparing genetic maps of L. angustifolius to the reference genome sequences of Medicago truncatula and Lotus japonicus Nelson et al, 2010) and by comparing the genetic map of L. albus to the genome of M. truncatula (Phan et al, 2007a).…”
Section: A Genus Lupinus Lmentioning
confidence: 99%
“…Transcriptome sequencing has been reported for L. albus and L. luteus (Parra-Gonzalez et al, 2012;O'Rourke et al, 2013) and is underway for L. angustifolius and a range of New World lupin species. A reference genome sequence assembly for L. angustifolius is currently under construction , and a genome survey has been reported (Yang et al, 2013b). Genotyping-by-sequencing has been used to develop improved markers for anthracnose and phomopsis resistance in L. angustifolius Yang et al, 2013a).…”
Section: Impact Of Genomics For Crop Legumementioning
confidence: 99%
“…In addition, recent draft genome sequence studies on narrow-leafed lupin revealed the presence of a single LDC gene (Conant and Wolfe, 2008;Yang et al, 2013). As active copies of both ODC and LDC were not found in the same plant, divergence in the regulatory regions due to changes in the expression patterns of the LDC and ODC copies to reduce the dominant-negative effect might not have occurred during plant LDC evolution.…”
Section: Evolution Of Plant Ldc For the Production Of Alkaloidsmentioning
confidence: 99%
“…It is the third largest family of flowering plants and includes several crops that are of high economic value as major protein sources for humans and animals. Moreover, the genome sequences of multiple members of the legume family are available, including Medicago truncatula (barrel clover), Cicer arietinum (chickpea), Lotus japonicus (Japanese trefoil), Glycine max (soybean), Cajanus cajan (pigeon pea), Phaseolus vulgaris (common bean), Vigna radiata (mung bean) and Lupinus angustifolius (lupin) (Sato et al, 2008;Schmutz et al, 2010Schmutz et al, , 2014Varshney et al, 2011Varshney et al, , 2013Young et al, 2011;Jain et al, 2013;Yang et al, 2013;Kang et al, 2014). Within the legume family, different polyploidy events have occurred.…”
Section: Introductionmentioning
confidence: 99%